Inhibition of urothelial carcinoma through targeted type I interferon-mediated immune activation - Plote, Devin (Oncoimmunology, 2019)
Type I interferon (IFN-I) has potent anti-tumor effects against urothelial carcinoma (UC) and may be an alternative treatment option for patients who do not respond to Bacillus Calmette-Guerin. However, the mechanisms that mediate the IFN-I-stimulated immune responses against UC have yet to be elucidated. Herein, we evaluated the anti-tumor mechanisms of IFN-I in UC in human patients and in mice. Patient tumors from a Phase I clinical trial with adenoviral interferon-α (Ad-IFNα/Syn3) showed increased expression of T cell and checkpoint markers following treatment with Ad-IFNα/Syn3 by RNAseq and immunohistochemistry analysis in 25% of patients. In mice, peritumoral injections of poly(I:C) into MB49 UC tumors was used to incite an IFN-driven inflammatory response that significantly inhibited tumor growth. IFN-I engaged both innate and adaptive cells, seen in increased intratumoral CD8 T cells, NK cells, and CD11b(+)Ly6G(+) cells, but tumor inhibition was not reliant on any one immune cell type. Nonetheless, poly(I:C)-mediated tumor regression and change in the myeloid cell landscape was dependent on IL-6. Mice were also treated with poly(I:C) in combination with anti-PD-1 monoclonal antibody (mAb) to assess for additional benefit to tumor growth and animal survival. When used in combination with anti-PD-1 mAb, IFN-I stimulation prolonged survival, coinciding with inhibition of angiogenesis and enriched gene signatures of metabolism, extracellular matrix organization, and MAPK/AKT signaling. Altogether, these findings suggest IFN-I’s immune-driven antitumor response in UC is mediated by IL-6 and a collaboration of immune cells, and its use in combination with checkpoint blockade therapy can increase clinical benefit.